Role of β 2-Adrenoceptor Activation in Sepsis-Induced Renal Inflammation - Nakamura, Akio; Yanagawa, Yukishige (Current Immunology Reviews (Discontinued), 2009)
Endotoxemia caused by Gram-negative bacteria can result in sepsis and organ dysfunction, which includes kidney damage and renal failure. The renal β2-adrenoceptor (β2-AR) system has an anti-inflammatory influence on the cytokine network during the course of immunologic responses. The previous reports indicated that the administration of β2-AR agonists was found to attenuate the stimulation of renal TNF-α associated with lipopolysaccharide and Shiga toxin-2 of hemolytic uremic syndrome, which is considered to be a central mediator of the pathophysiologic changes. On the other hand, an altered expression and/or function of β2-AR have been considered to be a pathogenetic factor in some disease states; for example, allergy, heart failure, and renal failure. These observations would suggest that blockade of functional β2-AR activation might be associated with an increase risk for organ dysfunction following severe sepsis. In the present article, we review renal β2-AR pharmacology and new insights into the functional importance of β2-AR signaling cascade in sepsis. In addition, an in vivo β2-AR gene therapy for the replacement of lost receptors as a consequence of sepsis and the genomic information of β2-AR to identify groups of patients with a high risk of developing sepsis-induced acute renal failure are also described.
Keywords: innate immunity